2014
DOI: 10.1002/hyp.10136
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing ephemeral streams in a southern Ontario watershed using electrical resistance sensors

Abstract: Ephemeral streams are small headwater streams that only experience streamflow in response to a precipitation event. Due to their highly complex and dynamic spatial and temporal nature, ephemeral streams have been difficult to monitor and are in general poorly understood. This research implemented an extensive network of electrical resistance sensors to monitor three ephemeral streams within the same small headwater catchment in Southern Ontario, Canada. The results suggest that the most common patterns of netw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 29 publications
0
34
0
Order By: Relevance
“…Bhamjee and Lindsay, ), temperature loggers and electrical conductivity sensors (e.g. Goulsbra et al ., ; Peirce and Lindsay, ), as well as fibre‐optic distributed temperature sensing systems and thermal cameras mounted on low‐altitude drones. Permafrost‐dominated catchments offer the intriguing possibility of mapping changes in surface and subsurface flow where the subsurface boundary layer conditions are evolving over time.…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 99%
“…Bhamjee and Lindsay, ), temperature loggers and electrical conductivity sensors (e.g. Goulsbra et al ., ; Peirce and Lindsay, ), as well as fibre‐optic distributed temperature sensing systems and thermal cameras mounted on low‐altitude drones. Permafrost‐dominated catchments offer the intriguing possibility of mapping changes in surface and subsurface flow where the subsurface boundary layer conditions are evolving over time.…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 99%
“…In particular, small, inexpensive electrical resistance (ER) sensors can measure saturated flow conditions from which streamflow timing can be accurately inferred (Blasch et al 2002;Chapin et al 2014). In general, ER sensor data allow examination and evaluation of the variation in timing, duration, and frequency of intermittency among streams at high temporal resolution (e.g., Jaeger and Olden 2012;Goulsbra et al 2014;Peirce and Lindsay 2014). In fact, ER sensors modified from light sensors also have the advantage of simultaneously recording temperature (Adams et al 2006;Chapin et al 2014), thus allowing assessment of the interactions between flow and temperature regimes.…”
mentioning
confidence: 99%
“…Many of the technical limitations in previous ephemeral stream monitoring studies can be improved by using a paired‐sensor approach. Previous studies have used a single sensor to detect water presence and infer that the water was flowing (Constantz et al ., ; Blasch et al ., ; Adams et al ., ; Goulsbra et al ., ; Bhamjee & Lindsay, ; Goulsbra et al ., ; Peirce & Lindsay, ). However, the assumptions that once water is present in the channel it is immediately flowing, or will flow at all, can be misleading.…”
Section: Discussionmentioning
confidence: 98%
“…() created an electronic resistance (ER) sensor by removing the thermistor from the temperature sensors. Over time, refinements of the ER sensor design improved the accuracy and interpretation of the data (Blasch et al ., ; Goulsbra et al ., ; Bhamjee & Lindsay, ; Peirce & Lindsay, ). Later, Bhamjee and Lindsay () found that state loggers further simplified the interpretation of ephemeral streamflow monitoring records while reducing data volume and increasing the temporal resolution of observations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation